Rancang Bangun Sistem Pencatatan Keuangan Berbasis Web untuk UMKM Menggunakan Metode Waterfall - Muhammad Agung Zulfikar; Andre Junika Yusuf Firmansyah; Wahyu Edi Santoso; Ahmad Ilham (JURNAL KOMPUTER DAN TEKNOLOGI INFORMASI, 2026)
ABSTRACTGood financial management is one of the key factors for the success of Micro,Small, and Medium Enterprises (MSMEs) in running their businesses. However,the majority of MSMEs in Indonesia still rely on manual financial recordingwhich is prone to errors and difficult to analyze. This research develops a web-based Financial Recording System specifically designed to meet the needs ofMSMEs using the Waterfall software development method. The system featuresincome and expense transaction recording, transaction category management,financial report visualization, budget management, and report export. Systemdesign was conducted through several stages including requirements analysisusing Use Case Diagrams, process modeling with Activity Diagrams and DataFlow Diagrams (DFD), and database design using Entity Relationship Diagrams(ERD). The system was developed using modern web technologies with anintuitive and responsive interface. Functional testing using Black-Box Testingshowed that all main system features work according to the establishedspecifications. User satisfaction testing using Likert scale showed an averagesatisfaction level of 4.2 out of 5, indicating that the system is well accepted bytarget users. This system is expected to help MSMEs manage their businessfinances more efficiently, accurately, and in a structured manner.This is an open access article under the CC BY-SA license.